Molecular detection of entamoeba histolytica and entamoeba dispar infection among wild rats in Kuala Lumpur, Malaysia - Lau, Y.L.; Jamaiah, I.; Rohela, M.; Fong, M.Y.; Siti, C.O.S.; Siti, F.A. (The Malaysian Society of Parasitology and Tropical Medicine, 2014)
Entamoeba histolytica infection is the third-greatest parasitic disease responsible for death in the world. Wild rats harbouring E. histolytica can be the possible reservoir hosts for human amoebiasis. There were numerous studies on prevalence of intestinal parasites among wild rats in Malaysia but none has reported E. histolytica. Rats were captured from Sentul and Chow Kit areas, Kuala Lumpur, Malaysia. The preserved stool samples were used for microscopy examination and molecular analysis. Out of 137 samples collected, 12 were positive for E. histolytica / E. dispar / E. moshkovskii microscopically. Two E. histolytica (1.4%), 1 E. dispar (0.7%) and 6 mixed infections of E. histolytica and E. dispar (4.3%) were detected using PCR. This is the first report of molecular detection of E. histolytica/dispar infection among wild rats in Malaysia. This study provides useful information about the potential risks of zoonotic agents and the importance of developing control measures to prevent zoonotic transmission.